2021
DOI: 10.3390/cosmetics8030087
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Topical Dexpanthenol-Containing Spray and Cream in the Recovery of the Skin Integrity Compared with Petroleum Jelly after Dermatologic Aesthetic Procedures

Abstract: Moisturizers are commonly prescribed after laser and chemical peel aesthetic procedures, but the evidence regarding their efficacy and safety of such use is scarce. We conducted four single-blind, three-week, controlled studies to evaluate the efficacy and safety of topical Dexpanthenol-containing products (Bepantol® spray and Bepantol® cream) using petroleum jelly as a positive control. Skin recovery was assessed after four aesthetic procedures: (1) non-ablative facial laser resurfacing, (2) laser depilation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Formulations containing dexpanthenol contribute to smoothing and hydrating injured skin, after tattooing procedures, therefore reinforcing the ability to maintain the skin barrier integrity [139]. Furthermore, in comparison with petrolatum jelly, topical dexpanthenol promotes skin hydration without the formation of acneiform lesions, often developed due to the occlusiveness provided by formulations with petrolatum derivatives [140]. It was also confirmed that these long-lasting skin-moisturizing effects (over 24 hours), as well as a relocation of the water molecules into deeper layers of the SC [141], do not negatively impact the cutaneous microflora viability [142].…”
Section: Dexpanthenolmentioning
confidence: 99%
“…Formulations containing dexpanthenol contribute to smoothing and hydrating injured skin, after tattooing procedures, therefore reinforcing the ability to maintain the skin barrier integrity [139]. Furthermore, in comparison with petrolatum jelly, topical dexpanthenol promotes skin hydration without the formation of acneiform lesions, often developed due to the occlusiveness provided by formulations with petrolatum derivatives [140]. It was also confirmed that these long-lasting skin-moisturizing effects (over 24 hours), as well as a relocation of the water molecules into deeper layers of the SC [141], do not negatively impact the cutaneous microflora viability [142].…”
Section: Dexpanthenolmentioning
confidence: 99%
“…Other formulations with dexpanthenol were tested in healthy adult women who underwent non-ablative laser resurfacing, laser depilation, or chemical peel [ 96 ]. The tested formulations maintained skin integrity, promoted recovery of damaged skin, and reduced erythema, and were associated with significantly decreased TEWL and dermal temperature.…”
Section: How Dexpanthenol Can Help In Admentioning
confidence: 99%
“…They were presented in Japanese and English. These attributes are typically used in the sensory evaluation of skin [13,[24][25][26], except for the two types of softness.…”
Section: Sensory Evaluation Of Bare Skinmentioning
confidence: 99%
“…Currently, cosmetic manufacturers and research institutes that perform efficacy evaluations of cosmetics train professional assessors based on these or similar guidelines [10][11][12][13][14][15][16]. For example, Addor et al [13] evaluated the effect of moisturizing products by instrumental measurements and trained panelists. However, there is limited published information on the reliability of sensory evaluations.…”
Section: Introductionmentioning
confidence: 99%